PERKECAMBAHAN BENIH KOPI ARABIKA (Coffea arabica L.) VARIETAS GAYO I AKIBAT PENGUPASAN KULIT TANDUK DAN PEMBERIAN ZAT PENGATUR TUMBUH (ZPT) - Hairunnas, Hairunnas; Khadijah, Khadijah; yanti, Sastri deka (Universitas Gajah Putih, 2021)
Hairunnas “Germination Arabica coffee Seeds (Coffea arabica L.) Variety Gay Due to Peeling Off The Skin And Giving Growth Regulator” which is carried out as collaborative research between lecturers and students. This research was conducted at the Faculty of Agriculture- Agricultural Laboratory of Universitas Gajah Putih, Pegasing Aceh Tengah District with an altitude above sea level of 1,200 m and the degree of soil acidity (pH) was 6. The research was carried out in October 2019. The results showed that the stripping of hornbones had a significant effect on potential Growth and germination, the best yield was potential growth with the treatment without hornbill (B1) at the age of 55 days germinating. The use of growth regulators had a significant effect on the potential for growth, with the best yielding potential for the growth potential of 55 days after seedling with 200 cc / l (Z2) treatment. There is a very real interaction with the stripping of horn skin and the administration of growth regulators in the growth potential test. The best results were obtained in the interaction between treatment without horn skin (B1) and dosage of 200 cc / l (Z2) or (B1Z2).